0/1h-algorithm using a new high-sensitivity cardiac troponin I assay for early diagnosis of myocardial infarction. (3rd October 2022) - Koechlin, L; Boeddinghaus, J; Lopez-Ayala, P; Nestelberger, T; Wussler, D; Twerenbold, R; Zimmermann, T; Wildi, K; Miro, O; Martin-Sanchez, J; Keller, D; Christ, M; et al.
Abstract: Background: The clinical performance of the novel high-sensitivity cardiac troponin I EXL (hs-cTnI-EXL) assay is unknown so far. Purpose: We aimed to validate the clinical performance of the hs-cTnI-EXL assay and to derive and validate an hs-cTnI-EXL-specific 0/1h-algorithm for the early diagnosis of myocardial infarction (MI). Methods: This multicenter study included patients presenting to the emergency department with symptoms suggestive of myocardial infarction. Central adjudication of final diagnoses was performed by two independent cardiologists using all clinical information including cardiac imaging twice: first, using serial hs-cTnI-Architect (primary analysis) and second, using serial hs-cTnT-Elecsys (secondary analysis) concentrations in addition to those clinically used (hs)-cTn. Hs-cTnI-EXL was measured at presentation and at 1h. The primary objective was to directly compare diagnostic accuracy quantified by the area under the receiver-operating-characteristic curve (AUC) of hs-cTnI-EXL, hs-cTnI-Architect and hs-cTnT-Elecsys. Secondary objectives included the derivation and validation of an hs-cTnI- EXL-specific 0/1h-algorithm. Results: MI was the adjudicated final diagnosis in 204/1454 (14%) patients. At presentation, the AUC for hs-cTnI-EXL was 0.94 (95% CI, 0.93–0.96), being comparable to hs-cTnI-Architect (0.95; 95% CI, 0.93–0.96) and hs-cTnT-Elecsys (0.93; 95% CI, 0.91–0.95; Figure 1). In the derivation cohort (n=813), an optimal hs-cTnI-EXL-0/1h-algorithm was rule-out of MI with <9ng/L if onset of chest pain >3h or <9ng/L & 0h-1h-change <5ng/L, and rule-in with ≥160ng/L or 0h-1h-change ≥100ng/L. In the validation cohort (n=345), this hs-cTnI-EXL-0/1h-algorithm also performed well: rule-out in 56% of patients, negative predictive value 99.5% (95% CI, 97.1–99.9), sensitivity 97.8% (95% CI, 88.7–99.6), rule-in in 9% of patients, positive predictive value 83.3% (95% CI, 66.4–92.7), specificity 98.3% (95% CI, 96.1–99.3; Figure 2). Secondary analyses confirmed the findings using adjudication including serial measurements of hs-cTnT-Elecsys. Conclusions: Hs-cTnI-EXL has comparable diagnostic performance to the currently best-validated hs-cTnT/I assays. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swiss National Foundation, Swiss Heart Foundation